2017
DOI: 10.1530/jme-17-0023
|View full text |Cite
|
Sign up to set email alerts
|

The association of the lipidomic profile with features of polycystic ovary syndrome

Abstract: Polycystic ovary syndrome (PCOS) affects up to 18% of reproductive-aged women with reproductive and metabolic complications. While lipidomics can identify associations between lipid species and metabolic diseases, no research has examined the association of lipid species with the pathophysiological features of PCOS. The aim of this study was to examine the lipidomic profile in women with and without PCOS. This study was a cross-sectional study in 156 age-matched pre-menopausal women (18-45 years, BMI >20 kg/m;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…Moreover, no normal‐weight woman below 35 years of age required intervention because of her lipid status. It seems that screening should involve women older than 35, with developed T2DM or AH, and obese cases, because central obesity is treated as a main factor of dyslipidaemia in PCOS . Similar opinion was expressed by Glintborg and Andersen, who suggested that prospective screening of lipids and BP is not necessary in normal‐weight patients with no metabolic risk factors until after the age of 35 to 40, as it appears that also the risk of AH in PCOS is closely associated with BMI .…”
Section: Discussionmentioning
confidence: 84%
“…Moreover, no normal‐weight woman below 35 years of age required intervention because of her lipid status. It seems that screening should involve women older than 35, with developed T2DM or AH, and obese cases, because central obesity is treated as a main factor of dyslipidaemia in PCOS . Similar opinion was expressed by Glintborg and Andersen, who suggested that prospective screening of lipids and BP is not necessary in normal‐weight patients with no metabolic risk factors until after the age of 35 to 40, as it appears that also the risk of AH in PCOS is closely associated with BMI .…”
Section: Discussionmentioning
confidence: 84%
“…Further, previous studies focused in PCOS patients strictly diagnosed by the basic triad (polycystic ovaries, amenorrhea and hyperandrogenism) in absence of associated pathologies suggested minor changes in lipid metabolism. Only slightly increased LDL-cholesterol and decreased HDL-cholesterol, as well as total cholesterol, have been described [ 57 59 ]. In this line, in our study (only focused in PCOS patients without associated pathologies) we did not find changes in the levels of triglycerides, total cholesterol, LDLc and HDLc, glucose levels, hemoglobin A1c, insulin, and HOMA index.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent and unique metabolomic study centered in follicular niche demonstrated that mitochondrial dysfunction of cumulus cells can be important in the pathogenesis of PCOS [ 56 ]. Later on, three studies specifically focused on the lipid metabolism have allowed to define a lipidomic profile in PCOS patients compared with control women at different stages of menstrual cycle [ 57 ], or suffering from obesity [ 58 , 59 ].…”
Section: Introductionmentioning
confidence: 99%
“…USP2-205 and USP2-206 mRNA with 563 and 677 bases respectively were less learned than the previous three subtypes, encoding the protein composed of 137 and 167 amino acids. The USP2-203 and USP2-207 mRNA with 670 and 637 bases respectively only have introns without the ability of protein encoding 5 . These protein subtypes differ in the length and the amino acid composition of the N terminal of the protein.…”
Section: The Alternative Splicing Products Of Usp2 Gene and Their Dismentioning
confidence: 99%
“…Alternative splicing allows a single gene to produce two or more similar but distinct mature mRNA variants that expand the coding capabilities of eukaryotic genomes 2 - 4 . Abnormal alternative splicing of some disease-related genes is also associated with pathogenesis and therapeutics, such as metabolic alterations and therapeutic tools in diabetes mellitus 5 .Through alternative splicing, USP2 gene also can produce different splicing variants which have their specific roles 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%